2021
DOI: 10.1111/jocn.15653
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of nurses’ respect for patient privacy by patients and nurses: A comparative study

Abstract: Aims To determine whether nurses respect or violate patient privacy by comparing nurses’ and patients’ opinions. Background Although nurses want to respect patient privacy, they can sometimes violate patient privacy or not pay enough attention. Method This comparative and cross‐sectional study was conducted with 357 patients and 305 nurses in 12 public hospitals in Trabzon, Turkey. Data were collected with an information form and the Patient Privacy Scale. Reporting is consistent with the STROBE checklist for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…A study of patients and healthcare workers in an Indian hospital showed that patients have higher perceptions of privacy than healthcare workers ( 29 ). Therefore, medical and nursing staff should pay attention to the degree of perioperative patients’ physiological and psychological privacy protection when conducting medical-related operations ( 30 ), and improve the quality and level of medical services.…”
Section: Discussionmentioning
confidence: 99%
“…A study of patients and healthcare workers in an Indian hospital showed that patients have higher perceptions of privacy than healthcare workers ( 29 ). Therefore, medical and nursing staff should pay attention to the degree of perioperative patients’ physiological and psychological privacy protection when conducting medical-related operations ( 30 ), and improve the quality and level of medical services.…”
Section: Discussionmentioning
confidence: 99%
“…1 Because of the importance of the issue, many international declarations or regulations and national legislation of many countries have sought to safeguard this right. [2][3][4][5] The International Council of Nurses defines privacy as "Privacy is the principle of non-interference in one's personal matters, information or physical body." 2 The Turkish Nurses Association has stated that privacy and confidentiality are among the ethical principles and responsibilities of nurses.…”
Section: Anah Tar Ke LI Me Ler: Hemşirelik; Etik; Hasta Mahremiyeti; ...mentioning
confidence: 99%
“…51 A Greek study showed that patients had little idea of their rights 52 and nursing has a very important role in disseminating this knowledge and ethical principles, establishing a relationship of respect for patients' rights and privacy. [53][54][55] Intensive care unit patients often have memories of the environment as hostile and stressful, generating negative feelings of violation of their rights to dignity and privacy, lack of empathy, not being understood, delay in getting help and being subject to full control by health professionals. 56 Most patients are unaware of their rights 57 ; a study with the distribution of information cards to patients with methicillin-resistant S. aureus infection, which should be presented to the professionals with whom they would consult, showed that these patients are subject to discrimination and lack of knowledge, which makes its use questionable.…”
Section: Open Accessmentioning
confidence: 99%